Survey of Neonates in Pomerania (SNiP): Study design and cohort update. Issue 2 (31st January 2020) - Kantorczyk, Elisa; Domanski, Grzegorz; Lange, Anja Erika; Ittermann, Till; Allenberg, Heike; Zygmunt, Marek; Heckmann, Matthias
Abstract: Background: The health status of newborns is a major concern for parents and medical personnel. Recent studies have provided increasing evidence that factors from the foetal and perinatal periods of life influence health later in life. The "Follow‐up of the Survey of Neonates in Pomerania" (SNiP‐I‐Follow‐up) is the first follow‐up of the population‐based birth cohort study, SNiP‐I, established in north‐east Germany. Objectives: The primary aim of SNiP‐I‐Follow‐up study was the collection of longitudinal data on children and adolescents. The associations will be analysed between risk factors in pregnancy and the perinatal period and health status in infancy and later childhood. Population: The population‐based cohort study SNiP‐I was conducted in Pomerania in north‐east Germany between February 2002 and November 2008. All mothers from the SNiP‐I birth cohort were recontacted when their children were from 9 to 15 years of age. Design: The SNiP‐I‐Follow‐up study was carried out between December 2016 and August 2017 and is a questionnaire‐based survey. Methods: Physical development, health status, and social behaviour (school and leisure behaviour) of children were analysed using a questionnaire comprising medical, epidemiological, and socio‐economic data, associated health care risk factors, and life circumstances of newborns, children, and their parents. Preliminary results: Out of 5725 children invited to participate in the SNiP‐I‐Follow‐up study between December 2016 and August 2017, 29% (n = 1665) children participated in the SNiP‐I‐Follow‐up study, providing data on 1665 mothers‐child dyads. Responders had higher socio‐economic status, especially in relation to maternal education status. Conclusion: As a longitudinal birth cohort from rural Germany, the SNiP cohort will be a resource to address urgent research needs and contribute to overall population health.